Copper-based porous self-lubricating material and preparation method thereof

Copper-based porous self-lubricating materials are prepared through selective laser melting technology to form an internal pore structure to store lubricating media, solving the problem of lubricating performance attenuation under high temperature conditions, achieving efficient self-lubricating and friction-resistant wear performance, and improving the service life of mechanical parts.

CN119747682APending Publication Date: 2025-04-04WUHAN RES INST OF MATERIALS PROTECTION
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411795092.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively lubricate mechanical parts such as bearings and gears under high temperature conditions, and the viscosity of liquid lubricants decreases at high temperatures, resulting in attenuation of lubricating performance and may cause environmental pollution.

Method used

Selective laser melting technology is used to prepare copper-based porous self-lubricating materials. By controlling the laser power, scanning speed and spot diameter, an internal pore structure is formed to store lubricating media, and the self-lubricating ability and friction and wear resistance of the material are improved.

Benefits of technology

It achieves effective lubrication under high temperature conditions, extends the service life of mechanical parts, avoids lubricating oil pollution, and improves the applicability of copper-based materials in the field of lubrication.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119747682A_ABST
    Figure CN119747682A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-based porous self-lubricating material and a preparation method thereof, and belongs to the technical field of metal-based composite material manufacturing. The method comprises the following steps: S1, preparing dry CuSn10 powder for later use; s2, a selective laser melting technology is adopted, and selective laser scanning printing is conducted on the CuSn10 powder in an inert atmosphere at a certain temperature; the laser power of selective laser scanning printing is controlled to be 200-300 W, the scanning speed is controlled to be 200-300 m / s, the laser spot diameter is controlled to be 0.05 mm, and the single-layer printing thickness is controlled to be 0.02-0.06 mm; a sample piece is obtained; and S3, the sample piece is subjected to sample removal and surface machining treatment, and the copper-based porous self-lubricating material is obtained. The copper-based porous self-lubricating material with the porous structure is prepared through the selective laser melting technology, has the advantages of being simple in material component, simple in process and low in cost, achieves the function of storing lubricating media, and is suitable for occasions where oil supply is difficult, lubricating oil pollution is avoided and starting and stopping are frequent due to the self-lubricating characteristic. Good application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal-based composite material manufacturing, and in particular to a copper-based porous self-lubricating material and a preparation method thereof. Background Art

[0002] With the rapid development of modern industry, mechanical parts need to face more and more severe service conditions. According to statistics, in various fields of industrial production, mechanical failure problems caused by friction and wear account for 60%-80% of the total number of failed parts. Wear and failure of key mechanical parts such as bearings and gears is one of the main causes of mechanical equipment failure and failure. In industrial applications, the most commonly used method to improve the lubricity between mechanical parts is liquid lubrication technology, but ordinary liquid lubrication technology can no longer meet the service conditions of precision mechanical parts such as bearings and gears. In addition, under high temperature conditions, the viscosity of liquid lubricants will decrease exponentially, and the lubrication performance will decay sharply. Some lubricants containing special components will also bring environmental pollution problems.

[0003] Copper-based composite materials have good mechanical properties, excellent electrical conductivity, thermal conductivity and corrosion resistance, and are suitable for special working conditions such as chemical, current-carrying, heavy load, high temperature and vacuum. At present, the preparation methods of copper-based composite materials mainly include: powder metallurgy, liquid metal hot extrusion, template method, etc. The powder metallurgy method has simple process, convenient operation and high material utilization rate, but the mechanical ball milling process cannot rearrange the particles in the matrix, which makes the lubricating phase particles exist in disorder in the matrix. Liquid metal hot extrusion requires higher preparation temperature and special equipment. Template method is an effective method for directional assembly of particles of different scales (from nanometer to micrometer), but it is necessary to screen suitable template agents. In contrast, selective laser melting is a rapid melting and solidification molding process in additive manufacturing technology. Based on the molding mechanism of complete melting / solidification, the complex structure of the material is constructed by software modeling, which can easily realize the molding and processing of complex parts.

[0004] For example, the Chinese invention patent with publication number CN109746435A discloses a surface-modified high laser reflectivity metal powder and 3D printing method, in which the surface of aluminum, copper, aluminum alloy or copper alloy powder with high laser reflectivity is coated with nickel, cobalt or iron metal particles with high laser absorption rate by chemical plating, that is, the original high laser reflectivity powder is modified into high laser absorption rate powder, and the printing performance of high laser reflectivity metal powder in the 3D printing process is enhanced to achieve 3D printing of high laser reflectivity metal powder. Compared with conventional commercial aluminum, copper, aluminum alloy or copper alloy powder used in 3D printing, after surface modification and coating, its laser absorption rate and printing performance are improved, the sphericity of the powder does not change much, the powder spreading process is not affected, and the printed metal parts are dense and have good mechanical properties. Although the metal powder has good processability in 3D printing, the dense metal parts produced by it have poor storage performance of lubricating medium under lubrication conditions and poor adaptability in friction and wear applications.

[0005] In summary, the selective laser melting technology was designed and used to realize processing and forming, and a copper-based material with good oil storage capacity and friction and wear resistance was obtained, which improved the applicability of copper-based materials in the lubrication field and was of great significance for reducing mechanical failures caused by friction and wear. Summary of the invention

[0006] In view of the above-mentioned defects of the prior art, in a first aspect of the present invention, a method for preparing a copper-based porous self-lubricating material with convenient process, fine processing and excellent quality control is provided, comprising the following steps: S1. Prepare dry CuSn10 powder; S2. Selective laser melting technology is used to perform laser selective scanning printing on CuSn10 powder in an inert atmosphere and at a certain temperature; the laser power of laser selective scanning printing is controlled to be 200-300 W, the scanning speed is 200-300 m / s, the laser spot diameter is 0.05 mm, and the single-layer printing thickness is 0.02-0.06 mm; and a sample is obtained; S3. The sample is subjected to stripping and surface machining to obtain a copper-based porous self-lubricating material.

[0007] Preferably, the specific steps of S1 are as follows: CuSn10 powder is sieved through a 200-mesh standard sieve, and then dried at 80-150° C. for 3-6 h.

[0008] After weighing the raw material powder, use a 200-mesh standard sieve to sieve and premix to remove agglomerated large-size particles, so that the finer raw material powder is distributed more evenly, which helps to ensure the consistency of material performance.

[0009] Preferably, in S1, the components of the CuSn10 powder include, by weight percentage: 88.0%-91.0% Cu, 9.0%-12.0% Sn and inevitable impurities.

[0010] Further preferably, the content of the unavoidable impurities is less than 0.5%.

[0011] Preferably, in the S1, the CuSn10 powder is a spherical powder with a particle size of 10-60 μm.

[0012] CuSn10 alloy is a copper-based alloy containing about 10% tin, also known as tin bronze. It has excellent mechanical properties and good thermal and electrical conductivity. In addition, CuSn10 has good fluidity, high sphericity, and low oxygen content, making it suitable for processing by selective laser melting technology (such as 3D printing).

[0013] Preferably, the specific steps in S2 are as follows: using selective laser melting technology, CuSn10 powder is loaded into the powder bin of the laser selective area scanning printing equipment, and after spreading a layer of powder, it is introduced into the printing model; after introducing argon gas for purging, the fan and substrate heating are turned on, and laser selective area scanning printing is started after the temperature stabilizes; the laser power of the laser selective area scanning printing is controlled to be 200-300 W, the scanning speed is 200-300 m / s, the laser spot diameter is 0.05 mm, and the single layer printing thickness is 0.02-0.06 mm; argon gas is used as the protective gas during the scanning process, and the printing environment is positive pressure; and a sample is obtained.

[0014] Further preferably, the speed of the fan is 1-2 m / s; and the temperature of the substrate is 80-120°C.

[0015] 3D printing in an argon atmosphere can reduce the negative impact of raw material oxidation on the performance of copper-based porous self-lubricating composite materials. By controlling the speed of the fan to avoid excessive temperature in the workroom due to long-term laser operation, the impact of environmental factors on the printing process can be reduced. The substrate can preheat the CuSn10 alloy powder to reduce the risk of sample cracking.

[0016] Preferably, in S3, the sampling method is wire cutting.

[0017] Those skilled in the art may adopt appropriate methods to perform the sample removal. Among them, wire cutting is particularly suitable for the sample removal method of the present invention. Wire cutting can provide very high cutting accuracy, making the cutting surface of the bottom of the part smoother. Since there is no physical contact between the electrode wire and the workpiece during the wire cutting process, the risk of workpiece damage caused by cutting force is greatly reduced.

[0018] Preferably, in S3, the surface machining treatment includes milling and grinding; the sample is surface machined to a surface roughness of Ra0.7-Ra0.9.

[0019] In the second aspect of the present invention, a copper-based porous self-lubricating material with simple material components, good lubricating medium storage capacity and excellent friction and wear resistance is provided, which is prepared by the preparation method of the first aspect of the present invention.

[0020] Based on the above technical solutions, the design concept and principle of the present invention are as follows: Under high temperature conditions, copper exhibits the characteristics of solid lubrication, and has certain self-lubricating ability and friction reduction performance. Therefore, in the selection of components of the present invention, CuSn10 alloy is used for preparation. The present invention adopts selective laser melting technology, designs the molding process according to the properties of the raw materials, and optimizes and adjusts the parameters such as laser power, scanning rate, layer thickness, etc. to obtain a copper-based porous self-lubricating material with a porous structure inside, which can realize the function of storing lubricating medium. Among them, controlling the laser spot diameter and the single-layer printing thickness is used to ensure that the CuSn10 alloy powder is fully melted. The control of the scanning speed is intended to form a good temperature gradient during the processing process, reduce residual internal stress, and reduce internal structural defects of the material. When the laser power is lower than the selected value range of the present invention, too low laser power will cause the powder temperature to be too low, the grain growth is insufficient, the grain size is different, and the internal pores are disorderly and irregular; correspondingly, too high laser power will cause the powder temperature to be too high, the grains to grow excessively, and the formation of large-sized grains is not conducive to the formation of pores, while affecting the overall performance of the material. Appropriate laser power is conducive to forming a regular grain structure with excellent mechanical properties and obtaining the target pore structure.

[0021] The unique composition and structure of copper-based porous self-lubricating materials are conducive to solving the lubrication problem of parts under complex working conditions, and have great practical engineering significance in bearings, gears and other parts. Its grain size is small and uniform, the grain boundary structure is tight, the pore shape is regular and evenly distributed, and it has good mechanical and tribological properties; the internal pore structure can realize the function of storing lubricating media. Under working conditions, due to thermal effects, capillary effects, centrifugal forces and pumping effects, the lubricating medium stored in the pores continuously seeps out, and a stable lubricating medium transfer film with a certain load-bearing capacity is established on the contact surface to avoid direct contact between the friction pairs. When the work stops, due to the capillary force of the pores and the pressure difference between the upper and lower boundaries of the lubricating film, the lubricating oil is sucked into the pores and stored, waiting for the next work to precipitate, and the cycle repeats, thereby extending the service life of the material. The self-lubricating properties of copper-based porous self-lubricating materials are very suitable for occasions where oil supply is difficult, lubricating oil pollution needs to be avoided, and frequent start-stopping is required. Moreover, during processing, the printing strategy is designed by software. By adjusting the shape of the printed model, it can be directly processed into finished products or semi-finished blanks of complex structural parts, realizing the preparation of fine structures. The processing method is simple and easy to promote.

[0022] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention provides a method for preparing a copper-based porous self-lubricating material, which has the advantages of simple raw material components, convenient and easy-to-control process, and low production cost. Through fine and excellent quality control processing, a product with fine and dispersed metallographic overall structure, good strength and performance uniformity can be prepared.

[0023] The present invention provides a copper-based porous self-lubricating material, which has simple material components, a specific pore structure inside, excellent lubricating medium storage capacity and friction and wear resistance, and has good application prospects in the field of lubrication. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a microstructure image of the copper-based porous self-lubricating material prepared in Example 1; Figure 2 The surface microhardness distribution of the copper-based porous self-lubricating material prepared in Example 1; Figure 3 This is a microstructure image of the copper-based porous self-lubricating material prepared in Example 2; Figure 4 The surface microhardness distribution of the copper-based porous self-lubricating material prepared in Example 2; Figure 5 The mechanical properties of the cross section in the vertical direction of the surface structure of the copper-based porous self-lubricating material prepared in Example 2; Figure 6 The wear morphology of the copper-based porous self-lubricating material prepared in Example 2 when not immersed in oil; Figure 7 The oil immersion / wear morphology of the copper-based porous self-lubricating material prepared in Example 2 after oil immersion and drying; Figure 8 This is a microstructure image of the copper-based composite material prepared in Comparative Example 1; Fig. 9 This is the microstructure image of the copper-based composite material prepared in Comparative Example 2. DETAILED DESCRIPTION

[0025] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0026] Example 1 The preparation method of the copper-based porous self-lubricating material comprises the following steps: S1 and CuSn10 powders were sieved through a 200-mesh standard sieve and then placed in a vacuum oven at 80 °C for 5 h to complete drying; S2. Use selective laser melting technology to load CuSn10 powder into the powder bin of laser selective scanning printing equipment, spread a layer of powder and introduce it into the printing model; after argon gas washing, turn on the fan and substrate heating, set the fan speed to 1m / s, and the substrate temperature to 100 ℃. After the temperature stabilizes, start laser selective scanning printing; control the laser power of laser selective scanning printing to 200 W, the scanning speed to 200 m / s, the laser spot diameter to 0.05 mm, and the single-layer printing thickness to 0.02 mm; use argon as the protective gas during the scanning process, and the printing environment is positive pressure; obtain the sample; S3. The printed sample is removed by wire cutting. After removal, the sample is surface machined to a roughness of Ra0.8 to obtain a copper-based porous self-lubricating material.

[0027] Example 2 The preparation method of the copper-based porous self-lubricating material comprises the following steps: S1 and CuSn10 powders were sieved through a 200-mesh standard sieve and then placed in a vacuum oven at 100 °C for 3 h to complete drying; S2. Using selective laser melting technology, put CuSn10 powder into the powder bin of laser selective scanning printing equipment, spread a layer of powder and introduce it into the printing model; after argon gas washing, turn on the fan and substrate heating, set the fan speed to 1m / s, and the substrate temperature to 120℃. After the temperature stabilizes, start laser selective scanning printing; control the laser power of laser selective scanning printing to 300 W, the scanning speed to 300 m / s, the laser spot diameter to 0.05 mm, and the single-layer printing thickness to 0.02 mm; use argon as the protective gas during the scanning process, and the printing environment is positive pressure; obtain the sample; S3. The printed sample is removed by wire cutting. After removal, the sample is surface machined to a roughness of Ra0.8 to obtain a copper-based porous self-lubricating material.

[0028] Example 3 The preparation method of the copper-based porous self-lubricating material comprises the following steps: S1 and CuSn10 powders were sieved through a 200-mesh standard sieve and then placed in a vacuum oven at 100 °C for 3 h to complete drying; S2. Using the selective laser melting technology, the CuSn10 powder was loaded into the powder bin of the laser selective scanning printing equipment, and after a layer of powder was spread, it was introduced into the printing model; after the argon gas was introduced for washing, the fan and substrate heating were turned on, the fan speed was set to 2m / s, the substrate temperature was set to 80 ℃, and the laser selective scanning printing was started after the temperature stabilized; the laser power of the laser selective scanning printing was controlled to be 300 W, the scanning speed was 200 m / s, the laser spot diameter was 0.05 mm, and the single-layer printing thickness was 0.02 mm; argon gas was used as the protective gas during the scanning process, and the printing environment was positive pressure; the sample was obtained; S3. The printed sample is removed by wire cutting. After removal, the sample is surface machined to a roughness of Ra0.7 to obtain a copper-based porous self-lubricating material.

[0029] Example 4 The preparation method of the copper-based porous self-lubricating material comprises the following steps: S1 and CuSn10 powders were sieved through a 200-mesh standard sieve and then placed in a vacuum oven at 100 °C for 3 h to complete drying; S2. Using selective laser melting technology, CuSn10 powder was loaded into the powder bin of the laser selective scanning printing equipment, and a layer of powder was spread before introducing the printed model; after argon gas was introduced for washing, the fan and substrate heating were turned on, the fan speed was set to 2m / s, the substrate temperature was set to 150°C, and the laser selective scanning printing was started after the temperature stabilized; the laser power of the laser selective scanning printing was controlled to be 300 W, the scanning speed was 300 m / s, the laser spot diameter was 0.05 mm, and the single-layer printing thickness was 0.06 mm; argon gas was used as the protective gas during the scanning process, and the printing environment was positive pressure; the sample was obtained; S3. The printed sample is removed by wire cutting. After removal, the sample is surface machined to a roughness of Ra0.9 to obtain a copper-based porous self-lubricating material.

[0030] Comparative Example 1 The preparation method of the copper-based composite material comprises the following steps: S1 and CuSn10 powders were sieved through a 200-mesh standard sieve and then placed in a vacuum oven at 100 °C for 3 h to complete drying; S2. Using selective laser melting technology, put CuSn10 powder into the powder bin of laser selective scanning printing equipment, spread a layer of powder and introduce it into the printing model; after argon gas washing, turn on the fan and substrate heating, set the fan speed to 1m / s, and the substrate temperature to 120 ℃. After the temperature stabilizes, start laser selective scanning printing; control the laser power of laser selective scanning printing to 100 W, the scanning speed to 100 m / s, the laser spot diameter to 0.05 mm, and the single-layer printing thickness to 0.02 mm; use argon as the protective gas during the scanning process, and the printing environment is positive pressure; obtain the sample; S3. The printed sample is removed by wire cutting. After removal, the sample is surface machined to a roughness of Ra0.8 to obtain a copper-based composite material.

[0031] Comparative Example 2 The preparation method of the copper-based composite material comprises the following steps: S1 and CuSn10 powders were sieved through a 200-mesh standard sieve and then placed in a vacuum oven at 100 °C for 3 h to complete drying; S2. Using selective laser melting technology, put CuSn10 powder into the powder bin of laser selective scanning printing equipment, spread a layer of powder and introduce it into the printing model; after argon gas washing, turn on the fan and substrate heating, set the fan speed to 1m / s, and the substrate temperature to 120℃. After the temperature stabilizes, start laser selective scanning printing; control the laser power of laser selective scanning printing to 400 W, the scanning speed to 100 m / s, the laser spot diameter to 0.05 mm, and the single-layer printing thickness to 0.02 mm; use argon as the protective gas during the scanning process, and the printing environment is positive pressure; obtain the sample; S3. The printed sample is removed by wire cutting. After removal, the sample is surface machined to a roughness of Ra0.8 to obtain a copper-based composite material.

[0032] Test Example 1 This test example studies the comprehensive performance of the copper-based porous self-lubricating material of the representative embodiment of the present invention in application. The test items and methods are as follows: The friction performance of the samples was tested using a reciprocating friction and wear tester, and GCr15 balls were used for the friction pair; The metallographic structure of the samples was characterized by metallographic microscope; The surface hardness distribution of the sample was tested using a Vickers hardness tester; The mechanical properties of the samples in the vertical cross-section direction were tested using a nanoindenter. The wear morphology of the samples was characterized by scanning electron microscopy; In order to test the oil storage performance of copper-based porous self-lubricating materials, a comparative test was carried out between the oil-immersed and dried samples and the original samples.

[0033] Depend on Figure 1 It can be seen that the copper-based porous self-lubricating material prepared in Example 1 has regularly distributed lotus-shaped pores inside, which can realize the oil storage function. Figure 2 It can be seen that the surface hardness of the copper-based porous self-lubricating material prepared in Example 1 is evenly distributed.

[0034] Depend on Figure 3 It can be seen that the copper-based porous self-lubricating material prepared in Example 2 has small and regular lotus-shaped pores distributed inside. Figure 4 It can be seen that the surface hardness of the copper-based porous self-lubricating material prepared in Example 2 is evenly distributed. Figure 5 It can be seen that the copper-based porous self-lubricating material prepared in Example 2 has uniform mechanical properties along the cross section in the vertical direction. The above results all confirm that the copper-based porous self-lubricating material of the present invention has uniform and reliable mechanical properties.

[0035] Depend on Figure 6 , 7By comparison, it can be seen that the copper-based porous self-lubricating material prepared in Example 2 can realize the oil storage function. After the friction and wear test of the non-oil-immersed sample, clear wear marks can be seen on the surface; the sample treated with oil immersion is only slightly worn, which proves that the lubricating medium stored in the pores is released during the friction process, greatly reducing the wear of the material. The above test results all prove that the copper-based porous self-lubricating material described in the present invention can realize the oil storage function.

[0036] Test Example 2 In this test example, the above method is used to characterize the microstructure of the copper-based composite materials prepared in Comparative Examples 1 and 2.

[0037] When the processing parameters of laser selective scanning printing are not within the scope of the process design of the present invention, such as Figure 8 As shown, compared with Examples 1 and 2, the laser power of Comparative Example 1 is lower, and the laser energy is difficult to fully melt the CuSn10 alloy powder, resulting in insufficient and uneven grain growth inside the prepared sample, forming a structure with different sizes and disordered growth directions, and a large number of irregularly shaped and large pores inside, which greatly affects the mechanical properties of the material. Fig. 9 As shown, compared with Examples 1 and 2, the laser power of Comparative Example 2 is higher, and the excessive laser energy leads to excessive growth of the grain structure. The prepared sample has a coarse grain structure, and the pores are of different sizes and randomly distributed. The coarse grains have a serious negative impact on the mechanical properties of the material. Comparative Examples 1 and 2 do not achieve the design effect of the present invention.

[0038] In summary, the copper-based porous self-lubricating material of the present invention has a regular pore structure and can realize the oil storage self-lubricating function; the copper-based porous self-lubricating material obtained by the preparation method provided by the present invention has a uniform organizational structure, uniform mechanical properties, and good friction and wear properties, and has good application prospects in the field of lubrication.

[0039] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for preparing a copper-based porous self-lubricating material, characterized in that: The steps include: S1. Prepare dry CuSn10 powder; S2. Selective laser melting technology is used to perform laser selective scanning printing on CuSn10 powder in an inert atmosphere and at a certain temperature; the laser power of laser selective scanning printing is controlled to be 200-300 W, the scanning speed is 200-300 m / s, the laser spot diameter is 0.05 mm, and the single-layer printing thickness is 0.02-0.06 mm; and a sample is obtained; S3. The sample is subjected to stripping and surface machining to obtain a copper-based porous self-lubricating material.

2. The method for preparing a copper-based porous self-lubricating material according to claim 1, characterized in that: The specific steps of S1 are as follows: CuSn10 powder is sieved through a 200-mesh standard sieve, and then dried at 80-150° C. for 3-6 hours.

3. The method for preparing the copper-based porous self-lubricating material according to claim 1, characterized in that: In the S1, the components of the CuSn10 powder include, by weight percentage, 88.0%-91.0% Cu, 9.0%-12.0% Sn and inevitable impurities.

4. The method for preparing the copper-based porous self-lubricating material according to claim 3, characterized in that: The content of the unavoidable impurities is less than 0.5%.

5. The method for preparing the copper-based porous self-lubricating material according to claim 1, characterized in that: In the S1, the CuSn10 powder is a spherical powder with a particle size of 10-60 μm.

6. The method for preparing a copper-based porous self-lubricating material according to claim 1, characterized in that: The specific steps in S2 are as follows: using selective laser melting technology, CuSn10 powder is loaded into the powder bin of the laser selective scanning printing equipment, and after spreading a layer of powder, it is introduced into the printing model; after introducing argon gas for purging, the fan and substrate heating are turned on, and laser selective scanning printing is started after the temperature stabilizes; the laser power of the laser selective scanning printing is controlled to be 200-300 W, the scanning speed is 200-300m / s, the laser spot diameter is 0.05 mm, and the single-layer printing thickness is 0.02-0.06 mm; argon gas is used as the protective gas during the scanning process, and the printing environment is positive pressure; and a sample is obtained.

7. The method for preparing the copper-based porous self-lubricating material according to claim 6, characterized in that: The speed of the fan is 1-2 m / s; the temperature of the substrate is 80-120°C.

8. The method for preparing a copper-based porous self-lubricating material according to claim 1, characterized in that: In S3, the method of removing the sample is wire cutting.

9. The method for preparing a copper-based porous self-lubricating material according to claim 1, characterized in that: In S3, the surface machining treatment includes milling and grinding; the sample is subjected to surface machining treatment until the surface roughness is Ra0.7-Ra0.

9.

10. A copper-based porous self-lubricating material, characterized in that: The method is prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Surface modified metal powder with high laser reflectivity and 3D printing method

    CN109746435A